Semiotic Analysis of Tourism Soft-Selling: Decoding Short Films as Persuasive Narratives - Sandra, Ni Putu Anindhitha Ayesha; Noina, Ni Made Karunia (Universitas Multimedia Nusantara, 2024)
Tourism marketing plays a crucial role in promoting destinations and attracting tourists. Nevertheless, tourism marketers are finding it increasingly difficult to attract the interest of potential travelers in a crowded digital environment. Short films have become a popular and effective medium to market destinations and influence tourist behavior due to their visually captivating storytelling and ability to evoke emotions in a short duration. Studying the impact of short films on tourism marketing is essential to comprehend their influence on tourist motivations, destination perceptions, and purchasing decisions. Therefore, this study aims to analyze the persuasion strategies used in promoting various tourist destinations through short films. By conducting a descriptive qualitative study, this study seeks to understand various semiotic elements and narratives in their short films to create persuasive messages that appeal to potential tourists. The analysis of these short films as persuasive narratives will provide insights into how cultural meanings are constructed and communicated through tourism marketing. By understanding the semiotic elements and persuasive narratives employed in these short films, we can gain a deeper understanding of how persuasive messages are crafted and how they influence tourists' perceptions and decision-making processes. Keywords: semiotics; short film; tourism; promotional; persuasive narrative